2018
DOI: 10.1039/c8nj04978e
|View full text |Cite
|
Sign up to set email alerts
|

Photo-induced synthesis of chiral galaxamide analogs and the biological activities against human tumor cells

Abstract: Two chiral analogs of galaxamide were synthesized by a photoinduced cyclization reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Galaxamide is defined as cyclo-(L-Leu-L-N-Me-Leu-L-Leu-L-Leu-L-N-Me-Leu Leu). The structural modification of galaxamide is initiated by splitting the amide bond the peptide sequence, followed by the introduction of phthalimide and photoinduced clization of linear peptides, as reported in our previous research [12,13]. In the pres study, the photoinduced substrate linear peptide is prepared by a liquid-phase metho as shown in Scheme 1.…”
Section: Synthesismentioning
confidence: 99%
See 2 more Smart Citations
“…Galaxamide is defined as cyclo-(L-Leu-L-N-Me-Leu-L-Leu-L-Leu-L-N-Me-Leu Leu). The structural modification of galaxamide is initiated by splitting the amide bond the peptide sequence, followed by the introduction of phthalimide and photoinduced clization of linear peptides, as reported in our previous research [12,13]. In the pres study, the photoinduced substrate linear peptide is prepared by a liquid-phase metho as shown in Scheme 1.…”
Section: Synthesismentioning
confidence: 99%
“…N-Me-leucine used here was prepared by adopting the t-BOC-l cine and iodomethane as raw materials in the presence of TEA. Then, the nitrogen-term nal amino groups were masked with phthaloylglycyl chloride to obtain N-phthalimid During the photoinduced process, the chain-like molecule (linear peptide) was excited and formed intramolecular zwitterionic biradicals after the departure of MeOSiMe 3 , and then the donator-and acceptor-free radicals at each end connected with each other to produce the cyclic compound [12,13]. After coupling, the C 3 carbonyl peak of phthalimido at δ 180 ppm disappeared in the 13 C NMR spectrum, followed by a new sp 3 hybridized C 3 peak at δ 85 ± 5 ppm, which is the characteristic NMR peak position of C 3 after the IPETC reaction.…”
Section: Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Our group has successfully synthesized some analogs of natural cyclic peptides Sansalvamide A, Fenestin A and Galaxamide by this method. [17][18][19] We found that the synthesis of cyclopeptides analogs by SET would produce optical pure cyclopeptides in our previous research, which could be regarded as a useful tool to prepare cyclic peptides with specic conformations.…”
Section: Introductionmentioning
confidence: 96%
“…2). In our previous studies, we also found that the chemical environment of hydrogen atoms on the phthaloyl group was changed after cyclization, 14 which could be ascribed to the + Si(CH 3 ) 3 group leaving and the integration of the phthaloyl carbonyl chromophore, leading to the disappearance of the symmetric hydrogen atom of phthaloyl. Meanwhile, the shielding effect of the cyclic peptide skeleton thus shifted the resonance upfield.…”
mentioning
confidence: 99%